Times Matter, the Impact of Convective Dust Events on Air Quality in the Greater Phoenix Area, Arizona - K. Ardon‐Dryer; T. Aziz (GeoHealth)
Abstract Convective dust events are common in the greater Phoenix area over the summer. These short‐duration dust events degrade the air quality and pose a potential health threat to millions. In this study, 93 convective dust events that occurred in July and August 2015 to 2021 were examined to determine their impact on air quality. Seven PM10 stations were used to evaluate the changes in PM10 concentrations over different time intervals (10‐min, hourly, and daily). Out of these 93 dust events, only 15.1% had a daily average above the EPA PM10 daily threshold, however, these daily concentrations were 12.8 and 28 times lower compared to hourly and 10‐min concentrations (respectively) at the peak of the dust. 10‐minute PM10 concentrations were on average 2.2 ± 0.8 times higher than the hourly concentrations. The findings of this study demonstrated that the traditional methods that use daily or hourly averages underestimate the atmospheric PM10 concentrations during short convective dust events and therefore lower the estimated exposure. There is a need to consider shorter time intervals to capture the PM concentrations accurately and highlight the importance of real‐time monitoring and accurate characterization of short‐duration events to assess their impacts on air quality and human health.